Protective Effect of Conditioned Medium of Immortalized Human Stem Cells from Exfoliated Deciduous Teeth Against Hair Graying Caused by X-Ray Irradiation via Its Antioxidative Activity - Yasuhiro Katahira; Eri Horio; Natsuki Yamaguchi; Jukito Sonoda; Miu Yamagishi; Satomi Miyakawa; Fumihiro Murakami; Hideaki Hasegawa; Izuru Mizoguchi; Takayuki Yoshimoto (Antioxidants)
Hair graying is one of the common visible signs of human aging, resulting from decreased or abolished melanogenesis due to the depletion of melanocyte stem cells through excess accumulation of oxidative stress. Cell-free therapy using a conditioned medium (CM) of mesenchymal stem cells has been highlighted in the field of regenerative medicine owing to its potent therapeutic effects with lower regulatory hurdles and safety risk. Recently, we demonstrated that a CM of an immortalized stem cell line from human exfoliated deciduous teeth (SHED) has protective effects against a mouse model of ulcer formation via antioxidative and angiogenic activities mediated by HGF and VEGF. However, to date, no effective treatments for hair graying have been developed, and the effect of SHED-CM on hair graying remains unknown. In this study, we have investigated the effect of SHED-CM on a hair graying mouse model caused by X-ray irradiation. Repetitive subcutaneous administrations of SHED-CM greatly suppressed the development of hair graying, when compared to control medium, resulting in reduced cutaneous expression of 8-hydroxy-2′-deoxyguanosine, the major product of DNA damage induced by reactive oxygen species. Consistent with these in vivo results, SHED-CM significantly inhibited the cell death caused by X-ray irradiation in melanoma cell line B16F10 cells. Immunodepletion of HGF or VEGF in the SHED-CM revealed that this inhibition was due to suppression of the generation of reactive oxygen species, which was mainly mediated by HGF and probably VEGF. These results suggest that SHED-CM has protective effects against hair graying via its antioxidative activity.